Complaint Defiction and Ultimum Remedium in the Perspective of Positivism (Roman) Law School, and Realism, and Sociology, and Utilitarism and Freie Recht Slehre (Anglo-American) - Youngky Fernando (Journal Equity of Law and Governance, 2023)
Wetboek van Strafrecht voor Nederlandsch-Indie or Wetboek van Strafrecht or the Penal Code or the Criminal Code or Criminal Code consists of the First/First Book (Article 1 to Article 103. Concerning General Regulations) and Second Book (Article 104 to/d Article 488. Concerning Crimes) and the Third Book (Articles 489 to Article 569. Regarding Violations).At first Crimineel Wetboek voor Het Koninkrijk Holland (WvS) was made in 1795 and enforced in 1809. Then France colonized the Netherlands, and the Penal Code was born from 1811 to 1813. After the Netherlands became independent, Wetboek van Strafrecht was born in 1881, it was enforced in 1886, and Wetboek was born van Strafrecht voor Nederlandsch-Indie based on Koninklijk Betsuit (order of the king) February 10 1866. About Crimes for Europeans Juncto Algemeene Politie Strafreglement based on Ordonnantie 15 June 1872. About Crimes for Europeans. Juncto Wetboek van Strafrecht voor Nederlandsch-Indie based on Ordonnantie May 5 1872.